Cerium and zinc co-doped nickel oxide hole transport layers for gamma-butyrolactone based ambient air fabrication of CH3NH3PbI3 perovskite solar cells - Choi, Fatma Pinar Gokdemir; Alishah, Hamed Moeini; Gunes, Serap (ELSEVIER, 2021)
Cerium and zinc co-doped nickel oxide (NiOx) hole transporter layers (HTLs) developed for boosting the efficiency and stability of inverted methylammonium lead tri-iodide (CH3NH3PbI3) based glove box-free fabricated solar cells. Combining our humidity resistive gamma butyrolactone-based perovskite deposition route with an optimum doping ratio of NiOx:Zn-Ce (18:6 mmol %) layers, power conversion efficiencies boosted from 10.04% to 14.47% and stability is increased under aging conditions. This performance enhancement was questioned over NiOx layers, quality of perovskite layer and the interface between charge transport layers and perovskite. Zn doping increased the electrical conductivity while incorporation of Ce created a positive impact on surface morphology and interface quality by a decreased roughness compared to the only Zn doped layers. The work function, hole mobility and concentration were found to increase with co-doping. Besides, the trap density of the perovskite layer is lessened, hindering unfavorable charge recombination confirmed by space charge limited current (SCLC) and photoluminescence (PL) analysis.
Keywords: Inverted perovskite solar cells; Ambient air deposition; Doping; Cerium; Zinc; Sol-gel; NiOx; Hole transport layer; ACHIEVING HIGH-PERFORMANCE; EXTRACTION LAYER; HIGHLY EFFICIENT; NIO NANOCRYSTALS; PLANAR; CH3NH3PBI3; SOLVENT; FILMS; STOICHIOMETRY; IMPACT; Chemistry; Materials Science; Physics